Activation of Factor X by Factor VIIa Complexed with Human-mouse Tissue Factor Chimeras Requires Human Exon 3 - Fang, Carrie H; Lin, T-C; Guha, Arabinda; Nemerson, Yale; Konigsberg, William H (Thrombosis and Haemostasis, 1996)
In an attempt to define sequence elements in human and mouse tissue factor (TF) that are responsible for the species specificity observed in their interaction with human factor VIIa (HVIIa), we constructed human-mouse chimeric TF cDNAs, inserted them into plasmid vectors, and induced their expression in E.coli. Assays for procoagulant activity were carried out with the resulting E. coli lysates using (HVIIa) human and mouse (MVIIa). The ratio of the procoagulant activities, HVIIa/MVIIa, revealed that human TF exon 3 was essential for activity when the TF:VIIa complex was formed with HVIIa. By ligating the maltose binding protein (MBP) gene to TF cDNAs it was possible to construct, express and purify MBP-TF chimeras as well as to estimate their specific activities. With selected MBP-TF chimeras and HVIIa we determined kinetic parameters for the activation of human factor X. Replacement of exon 3 in human TF cDNA with the corresponding exon from mouse TF cDNA resulted in both lower affinity for HVIIa and failure to convert bound HVIIa into a potent protease